2015
DOI: 10.5799/ahinjs.01.2015.01.0482
|View full text |Cite
|
Sign up to set email alerts
|

Determining smoking level of hospital employees and the evaluation of the smoke-free air zone applications

Abstract: Objective: The aim of this study is to define the health knowledge, cigarette smoking behaviors, attempts and successes to quit smoking and obstacles indicated by the ones who still smoke among a Training and Research Hospital staff four years after the application of the law "Smoke Free Air Zone". Methods: A questionnaire developed by the researchers is used for this cross sectional research. It questions the sociodemographic features and thoughts and attitudes about the "Smoke Free Air Zone" and "Smoke Free … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
3
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 7 publications
1
3
0
1
Order By: Relevance
“…Comparison of the rate of smoking reported in the present study with that reported in previous studies conducted in Turkey showed a decrease in the rate of smoking over the past years. The results reported in some recent studies are consistent with those reported in this study, 17,18 whereas studies conducted in the past report a higher incidence of smoking 19,20 . The results of the present study showed that the smoking rate decreased during the COVID‐19 pandemic in Turkey, which complies with the World Health Organization recommendations most and the world leader in fighting against tobacco.…”
Section: Discussionsupporting
confidence: 92%
“…Comparison of the rate of smoking reported in the present study with that reported in previous studies conducted in Turkey showed a decrease in the rate of smoking over the past years. The results reported in some recent studies are consistent with those reported in this study, 17,18 whereas studies conducted in the past report a higher incidence of smoking 19,20 . The results of the present study showed that the smoking rate decreased during the COVID‐19 pandemic in Turkey, which complies with the World Health Organization recommendations most and the world leader in fighting against tobacco.…”
Section: Discussionsupporting
confidence: 92%
“…Dugas et al also defined smoking as a known risk factor for sleep disorders ( Dugas et al, 2017 ). In the study conducted to determine the smoking levels of hospital workers, the rate of smoking was determined to be 29.6% in Turkey ( Koç et al, 2015 ). In parallel with the studies, smokers in the sample group were found to be 31%, and the PSQI scores of those who smoked 11 or more per day were higher than those who did not smoke.…”
Section: Discussionmentioning
confidence: 99%
“…18.7% -max. 66.2%) [11,12] . It was observed that the general average of actively smoking in hospital physicians was much lower.…”
Section: Discussionmentioning
confidence: 99%